Do nada ao espectro: variações metafísicas a partir da obra de Pierre Clastres - Ferreira, Rafael Poveron (2025)
In Pierre Clastres' work, the surreptitious nature of Heidegger's influence can be glimpsed in several passages, when the vocabulary of Heideggerian philosophy suddenly emerges: "true place of being" (2003 [1974], p. 141), "first language, addressed only to thought" (2003 [1974], p. 141), "absolute repositories of the human" (1990 [1974], p. 141). This work seeks to systematize and understand this philosophical influence on the author's ethnological work. Thus, it is demonstrated that the ethnologist operated creative twists of Heideggerian concepts. The resulting theoretical creativity allows Pierre Clastres to approach contemporary works, such as that of Maniglier (2015), thus distancing him from the perception according to which the author would be the heir of a phenomenological tradition (Abensour, 1987).In this sense, this work interprets these twists of Heideggerian concepts as a “controlled equivocation” (Viveiros de Castro, 2004) between Western and indigenous philosophy. Clastres thus opens up a terrain that allows for an expanded metaphysical comparativism, which this dissertation focuses on, focusing especially on language and indexicals. Thus, this dissertation aims to excavate the terrain of equivocation in which Clastres and the Amerindians inhabit – a jocular variation of Agamben’s project, which “excavated the terrain of Being in which Man inhabits” (Negri, 2011, p. 336).